Research of Changes in Quantities and Qualities of Leaf Volatile Oils of Zhumeria majdae Rech. f. & Wendelbo in Different Stages of Growth - AA Majrouhi (Institue of Medicinal Plants, ACECR, 2009)
Background: The monotypic Iranian Zhumeria majdae (Lamiaceae), known locally by the name of Mohrekhosh, was recently described as the first member of a new genus (Zhumeria). It has a limited geographical rang in southern Iran at Hormozgan province. The leaves have been used for many years as curative and antiseptic. Objective: The aim of the present study was to detect and compare the constituents of the essential oils of Zhumeria majdae in different stages of growth. Methods: In this research, the constituents of essential oils of Zhumeria majdae leaves at the before of flowering and the end of flowering in Geno mountain of Hormozgan province were analyzed via GC and GC/MS and compared together. Results: The oil yield of the dried leaves by hydrodistillation at two stage were 7.5 and 9.3%, respectively (v/w). At the essential oils of the before of flowering and the end of flowering stages, 22 and 16 compounds ,accounting for 99.9% of the oil, were identified. Conclusion: The numbers and contents of constituents of essential oils of Zhumeria majdae in different stages of growth are different.